Perceived Quality and Relationship Quality as Antecedents and Predictors of Loyalty in the Chemical Industry: A Literature Review - Andreas Samudro; Ujang Sumarwan; Eva Z. Yusuf; Megawati Simanjuntak (European Scientific Journal, ESJ, 2018)
Several kinds of research in the past examined relationship quality as antecedents in B2B industries. The literature review extends a prior study by linking perceived quality with relationship quality as antecedents and predictors of customer loyalty. This study is a review of customer loyalty antecedents with the chemical industry as a content object. Perceived quality has two dimensions of tangible product and service. Referring to past research, there is no single universal relationship quality framework. This literature study refers to the relationship quality framework with a content of trust, satisfaction, and commitment. The authors investigate the relationship between perceived quality with trust and satisfaction, trust with commitment, commitment with loyalty, and satisfaction with loyalty. Every construct describes the definition and connection among constructs. Some chemicals industries are put as object examples to explain constructs in industry practice. This literature review finds a developed framework with relevant constructs that influence loyalty in the B2B context. By understanding the framework and connection among constructs, firms can develop a relationship program purposely to achieve customer loyalty.